Library marketing, the National Electronic Library, library pedagogy - A. V. Sokolov (Библиосфера)
Stages of marketing development in general and library marketing in particular are considered. Prospects of library marketing development in Russia depend on the National Electronic Library project and the concept 3.0 of marketing. The historical continuity of library marketing and library pedagogy is demonstrated.